Living L'Arche : Stories of Compassion, Love, and Disability. - Reimer, Kevin S. (Bloomsbury Publishing PLC, 2009)
Living L'Arche explores the origins and characteristics of compassionate love in those who care for the disabled. It shows that authentic compassion is only distantly related to individual talent or will, and selfless care for others is not evoked on the basis of fair exchange or individual benefit. Instead, the craft of compassionate love is slowly learned from disabled persons living at the furthest margins of modern society. Based on a two-year scientific study of L'Arche communities, founded by Jean Vanier, in which disabled core members and caregiver assistants live together, the book sho.